Use of Blended Educational Methods in the Educational Process - Khikmatov Nodir Nazimdjanovich (Scholars Digest Publishing, 2023)
The problem of choosing the most effective innovative methods and technologies in the modern higher education system remains relevant. Innovative methods are methods based on the use of modern advances in science and information technology. Innovative methods, first of all, are aimed at optimizing the educational process, creating the most favorable conditions for mastering the educational material, which ultimately serves to increase the quality of education. Production ability today is becoming the main qualification characteristic of a teacher's activity and means moving to a higher level of organization of the educational process.
Keywords: Blended education, information technologies, integration, educational materials, modern pedagogical tools.